2017
DOI: 10.1111/tpj.13502
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of gene co‐expression networks reveals the evolution of functional modules

Abstract: Molecular evolutionary studies correlate genomic and phylogenetic information with the emergence of new traits of organisms. These traits are, however, the consequence of dynamic gene networks composed of functional modules, which might not be captured by genomic analyses. Here, we established a method that combines large-scale genomic and phylogenetic data with gene co-expression networks to extensively study the evolutionary make-up of modules in the moss Physcomitrella patens, and in the angiosperms Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 76 publications
5
81
0
Order By: Relevance
“…The proteins encoded by the lectin genes are part of a larger and complex interactome, and it will be difficult to relate the emergence of a new protein domain combination to existing pathways. Therefore, a combined analysis of these traditional approaches in combination with co-expression networks would be advantageous and could expand our knowledge since recent studies demonstrated that co-expression networks are conserved also across species [185,186]. At the same time, we cannot exclude the presence of minor mistakes in our dataset due to missing annotation of genes or unidentified protein domains.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins encoded by the lectin genes are part of a larger and complex interactome, and it will be difficult to relate the emergence of a new protein domain combination to existing pathways. Therefore, a combined analysis of these traditional approaches in combination with co-expression networks would be advantageous and could expand our knowledge since recent studies demonstrated that co-expression networks are conserved also across species [185,186]. At the same time, we cannot exclude the presence of minor mistakes in our dataset due to missing annotation of genes or unidentified protein domains.…”
Section: Discussionmentioning
confidence: 99%
“…Araport (Krishnakumar et al, 2014) and PlaNET (Ruprecht et al, 2017). This latter resource, PlaNET, 738 does host some B. distachyon datasets, but it is limited to the visualization and analysis of co-regulated 739 gene networks.…”
Section: Outlook: Embracing and Enhancing The Brachypodium Model Systmentioning
confidence: 99%
“…Recently, genomic analysis have been applied to study key events in the evolution of the green lineage such as terrestrialization (Delwiche and Cooper, 2015; de Vries et al, 2016). Nevertheless, the integration of genomics and transcriptomics to study the evolution of gene expression patterns in the green lineage has only recently been explored (Romero-Campero et al, 2013; Ruprecht et al, 2017). Photosynthetic organisms are particularly influenced by daily light/dark transitions as their main energy income is a very demanding light-dependent process.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, phylogenomic and transcriptomic data integration and analysis have been performed by gene co-expression networks construction (Romero-Campero et al, 2013; Gehan et al, 2015; Ruprecht et al, 2017) and a novel algorithm for the identification of potential orthologues called Multiple Best Bi-directional Hit (MBBH). Using clustering techniques, specific gene clusters or modules that showed a rhythmic daily regulation have been identified.…”
Section: Introductionmentioning
confidence: 99%